What if We Seem to Seem and Not Seem? Estimating the Unreasonable Price of Illusionism - Karak, Biplab (Problemos, 2024)
With its strategic consideration of phenomenal consciousness illusorily seeming to us, illusionism claims to deny phenomenality and thereby obviate the hard problem of consciousness. The problem with illusionism, however, is that, although its thesis appears persuasively simple, it strikes as absurd insofar as the phenomenal illusions themselves also seem as much as phenomenality, keeping no fundamental differences between the two. In short, it reinforces the same phenomenon/issue, i.e., phenomenality, that it claims to deny/avoid. This single absurdity is reflective of its self-refuting nature, and it alone is enough for a rejection of illusionism. However, does illusionism have any reasonable justification to defend itself in the face of the experientially undeniable reality of phenomenal consciousness? This paper attempts to find out if there is any such illusionist justification.